Takayasu arteritis: a rare case scenario - Dr. Madhu Singh; Prof (Dr). R. Dayal; Prof (Dr). Neeraj Kumar; Dr. Sheo Pratap Singh; Dr. L.K. Gupta; Dr. Neelam (Pediatric Review: International Journal of Pediatric Research, 2019)
Takayasu’s arteritis (TA), commonly known as “Pulseless disease”, is rare granulomatous arteritis, which affects large and medium-sized arteries, especially the aorta and its branches. Other arteries that can be affected are proximal portions of pulmonary, coronary, and renal arteries. Initially, mononuclear cell infiltrates in the adventitia leading to granuloma formation, followed by disruption of the elastic layer and subsequent massive medial and intimal fibrosis. These lesions result in segmental stenosis, occlusion, dilatation, and aneurysmal formation in the affected vessels.Diminished or absent pulses are present in 84-96% of patients, associated with limb claudication and blood pressure discrepancies between the two arms. The symptoms are secondary to the involved artery, and it may evolve into a life-threatening condition. The involvement of the carotid artery leads to ophthalmic artery hypoperfusion and causes the ocular ischemic syndrome. It usually affects young females during the second and the third decades of life but rare cases have been reported in children as young as 24 months of age. Although females are more likely to be affected in TA, males are also affected. In adults approximately 80% of patients with TA are women, although the female-to-male ratio varied from 9:1 in reports from Japan, 6.9:1 in Mexico to 1.2:1 in Israel.Aim of our report is to describe the case of a young female of 14 years of age. She presented with arterial hypertension and respiratory distress. CT Angiography showed Type IIb Takayasu Arteritis. ECHO revealed dilated cardiomyopathy with grade III diastolic dysfunction with decreased ejection fraction up to 20-25%. She was treated with steroids, anti-hypertensive drugs, and diuretics.